2010
DOI: 10.1182/blood-2010-05-286500
|View full text |Cite
|
Sign up to set email alerts
|

Autoimmune cytopenia in chronic lymphocytic leukemia: prevalence, clinical associations, and prognostic significance

Abstract: We analyzed prevalence, characteristics, clinical correlates, and prognostic significance of autoimmune cytopenia in patients with chronic lymphocytic leukemia. Seventy of 960 unselected patients (7%) had autoimmune cytopenia, of whom 19 were detected at diagnosis, 3 before diagnosis, and 48 during the course of the disease. Forty-nine patients had autoimmune hemolytic anemia, 20 had immune thrombocytopenic purpura, and 1 had both conditions. A clear association was observed between autoimmune cytopenia and po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
135
1
4

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 124 publications
(145 citation statements)
references
References 38 publications
5
135
1
4
Order By: Relevance
“…We confirm in this series, as previously reported, that lymphoproliferative disorders are frequently associated with wAIHA and that wAIHA may precede by months or even years the onset of lymphoma. Chronic lymphocytic leukemia (CLL), classically the leading cause of secondary AIHA [18], represented only 3/14 cases of lymphoproliferative disorders in the present series, and 4/15 cases in the previous series [5]. This low rate is probably explained by AIHA occurring mainly in patients with active CLL who are usually followed in Departments of hemato-oncology.…”
Section: Discussionmentioning
confidence: 50%
“…We confirm in this series, as previously reported, that lymphoproliferative disorders are frequently associated with wAIHA and that wAIHA may precede by months or even years the onset of lymphoma. Chronic lymphocytic leukemia (CLL), classically the leading cause of secondary AIHA [18], represented only 3/14 cases of lymphoproliferative disorders in the present series, and 4/15 cases in the previous series [5]. This low rate is probably explained by AIHA occurring mainly in patients with active CLL who are usually followed in Departments of hemato-oncology.…”
Section: Discussionmentioning
confidence: 50%
“…Various studies conducted in United State, Israel, Spain, England and Rome have reported a frequency of positive DAT in 4.5%, 7%, 4.3%, 7.7% and 3.7% of CLL patients respectively (Kyasa et al, 2003;Lischner et al, l988;Moreno et al, 2010;Hamblin et al, 1986;Mauro et al, 2000). However the prevalence of DAT positivity in our patients appears to be higher than these studies conducted in western world.…”
Section: Direct Coombs Test Positivity In B-chronic Lymphoid Leukemiamentioning
confidence: 97%
“…This highlights the importance of determining the origin of the cytopenia in CLL patients for both prognostic and therapeutic reasons (Clive et al, 2010;Moreno et al, 2010).…”
Section: Direct Coombs Test Positivity In B-chronic Lymphoid Leukemiamentioning
confidence: 99%
See 1 more Smart Citation
“…Autoimmune hemolytic anemia (AIHA) is a well-known complication of chronic lymphocytic leukemia (CLL), occurring in about 5-15% of the patients during the course of the disease [1,2]. There is no evidence-based strategy for the treatment of AIHA associated to CLL, especially in relapsed or resistant AIHA or when AIHA is associated with progressive CLL, because these patients are generally excluded from clinical trials.…”
Section: Introductionmentioning
confidence: 99%